Capacidad adquisitiva de los hogares de los estudiantes de la Universidad Nacional de Chimborazo y su incidencia en la inseguridad alimentaria ante la emergencia sanitaria, período 2020. - Estefanía Elizabeth, Villagómez Pérez (2021)
ABSTRACT The present project aims to investigate and analyze the relationship between the purchasing power of households with Food Insecurity and how its determinants affect the homes of students of the National University of Chimborazo. For which food insecurity measured through the Latin American and Caribbean Food and Agriculture Scale (ELCSA), taking as a time base the health emergency caused by the new virus COVID 19. The structure of this research has been detailed, in Chapter I: The Reference Framework, the introduction, the statement of the problem and finally the objectives to be achieved are stated. In Chapter II: The Theoretical Framework made the background of the investigation and the theoretical foundation detailed. In Chapter III: The Methodological Framework presented, the methodology applied and after that, the survey analyzed by means of statistical tables and graphs, from the information obtained from the online surveys that It was helpful for the study of the variables and by means of a probabilistic regression model the direct relationship that exists between the two variables is established. Finally, in Chapter IV: The conclusions and recommendations that could be deduced after the research studies are presented. Key Words: purchasing power, family income, consumption, food insecurity, access to food. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324